Clinical application of submandibular endotracheal intubation in craniomaxillofacial fracture - Kaifang Yuan; Qudong Liao; Meixing Ren; Lin Lu; Guotao Wu; Junwen Wang (Elsevier, 2024)
Objective: To explore the clinical application of submandibular endotracheal intubation in craniomaxillofacial fractures. Methods: The submandibular endotracheal intubation was used to treat 10 patients with cranio-maxillofacial fractures and contraindications to nasal intubation.Ventilator monitoring data including SPO2(oxygen saturation of blood), Freq,VT,MV,PEEP, PLAT and PEAK were monitored before and after the operation of submandibular endotracheal intubation. The technique of submandibular intubation was assessed intraoperatively and in the postoperative period. The outcomes and complications are presented. Results: The study included 10 patients aged between 18 and 63 years(6 males and 4 females). All patients had mandibular fractures, with 6 midface fractures (60 %), 5 nasal bone fractures (50 %), 6 zygomatic bone fractures (60 %). The procedure time ranged from 6 to 10 min (mean, 7.9 min). NO delayed extubation was performed in 10 cases. The technique has proved to be straightforward and satisfactory. A postoperative superficial infection occurred in 1 patients, whereas hypertrophic scars occurred in another 1 patients. Conclusion: Submandibular endotracheal intubation is a safe procedure for intraoperative airway control in maxillofacial trauma patients who present contraindication to nasotracheal intubation.